Preliminary Ruling 242-IP-2015 of the Andean Court of Justice. About the active legitimacy of administrative authorities to request preliminary ruling and the registration requirements applied to tactile marks - Indacochea, Juan Manuel (2018)
On August 24, 2015, the Andean Court of Justice issued the Preliminary Ruling 242-IP-2015, on the tactile mark consisting in the surface of the whisky bottle Old Parr. This Preliminary Ruling is the first one rendered by an international court about tactile marks. The purpose of this paper is to explain the application of the main registration requirements to new types of marks, in the light of the criteria explained in the aforementioned Preliminary Ruling. It also aims to analyze the previous jurisprudential development, concerning the active legitimacy of the Administrative Authorities of the Member Countries to optionally request Preliminary Rulings. That is the first question –or subject– addressed in the above-mentioned Preliminary Ruling since the interpretation was requested by an Administrative Authority of Colombia.